The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-29452013000100036
|View full text |Cite
|
Sign up to set email alerts
|

Limpeza clonal de mudas de videira infectadas por Xanthomonas campestris pv. viticola

Abstract: RESUMO -O cancro bacteriano da videira é causado por Xanthomonas campestris pv. viticola (Xcv). Visando à limpeza clonal de mudas de 'Red Globe', foram estudados: tamanho ideal de ápices e gemas axilares para cultivo em meio de Galzy modificado (MGM); efeito da termoterapia (38ºC/30 dias); e ação de antibióticos na eliminação de Xcv em videiras infectadas. Os percentuais de contaminação por Xcv e de regeneração foram analisados, e as plantas obtidas foram indexadas em meio ágar nutritivo-dextrose-extrato de le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(3 reference statements)
0
6
0
2
Order By: Relevance
“…[38]. In Vitis vinifera, the addition of streptomycin at 100 mg L -1 did not control the manifestation of bacterial canker, and after 40 days of in vitro cultivation, 100% of the explants remained with the bacterium [37]. Unlike these reports, our results for Eucalyptus microcorys showed that the addition of streptomycin at 250 mg L -1 did not reduce microbial manifestation in the culture medium; whereas at 100 mg L -1 , microbial manifestation decreased in 65% of the explants of individual 2.…”
Section: Reduction Of Microbial Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…[38]. In Vitis vinifera, the addition of streptomycin at 100 mg L -1 did not control the manifestation of bacterial canker, and after 40 days of in vitro cultivation, 100% of the explants remained with the bacterium [37]. Unlike these reports, our results for Eucalyptus microcorys showed that the addition of streptomycin at 250 mg L -1 did not reduce microbial manifestation in the culture medium; whereas at 100 mg L -1 , microbial manifestation decreased in 65% of the explants of individual 2.…”
Section: Reduction Of Microbial Manifestationmentioning
confidence: 99%
“…Streptomycin has been tested for controlling the manifestation of microorganisms on in vitro cultures of several species, such as Helianthus tuberosus [32], Persea americana [33], Solanun tuberosum [34], Rauwol a serpentina [35], Guadua angustifolia Kunth [36], Vitis vinifera [37], Butea monosperma (Lam.) Kuntze var.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal treatments could also be used in plants of Vitis. Silva et al (2013) failed to eliminate Xcv from in vitro plants using thermotherapy at 38°C for 30 days. Thermo-therapeutic treatments with dormant plant materials of Vitis at 48-52°C for 30-45 min (according to grapevine cultivars) are recommended for other bacterial plant pathogens (EFSA PLH Panel, 2015).…”
Section: Potential Risk Reducing Optionsmentioning
confidence: 99%
“…Atualmente, a técnica de cultura de tecidos é muito utilizada para propagação de plantas livres de patógenos e, no caso da videira, possibilita a obtenção de plantas com boa regeneração e livres de Xcv (SILVA et al, 2013). No entanto, requer longo tempo e ainda não está sendo utilizada em larga escala no Vale do Submédio São Francisco.…”
Section: Introductionunclassified